Can diffusion weighted magnetic resonance imaging help differentiate stroke from stroke-like events in MELAS?. Issue 2 (1st August 2000) - Oppenheim, C; Galanaud, D; Samson, Y; Sahel, M; Dormont, D; Wechsler, B; Marsault, C
Abstract : The precise mechanism of neurological symptoms in patients with mitochondrial myopathy, encephalopathy, lactic acidosis, and stroke-like episodes (MELAS) is still controversial. The diffusion weighted MR findings at the acute phase of a neurological event in MELAS are described and the pathophysiology of stroke-like lesion in the light of diffusion changes is discussed. Brain MRI was performed 2 days after the sudden onset of cortical blindness in a 25 year old patient with MELAS. Fluid attenuated inversion recovery (FLAIR) images showed multifocal cortical and subcortical hyperintensities located bilaterally in the frontobasal and the temporo-occipital lobes. Diffusion weighted images showed normal to increased apparent diffusion coefficient values in the acute left temporooccipital lesion and increased values in the older stroke-like lesions. These diffusion weighted findings support the metabolic rather than the ischaemic pathophysiological hypothesis for stroke-like episodes occurring in MELAS. Normal or increased apparent diffusion coefficient values within 48 hours of a neurological deficit of abrupt onset should raise the possibility of MELAS, especially if conventional MR images show infarct-like lesions.